Effects of spinal cord injury on body composition and metabolic profile – Part I. (November 2014) - Gorgey, Ashraf S.; Dolbow, David R.; Dolbow, James D.; Khalil, Refka K.; Castillo, Camilo; Gater, David R.
<x content-type="archive" xml:space="preserve">Abstract</x> Several body composition and metabolic-associated disorders such as glucose intolerance, insulin resistance, and lipid abnormalities occur prematurely after spinal cord injury (SCI) and at a higher prevalence compared to able-bodied populations. Within a few weeks to months of the injury, there is a significant decrease in total lean mass, particularly lower extremity muscle mass and an accompanying increase in fat mass. The infiltration of fat in intramuscular and visceral sites is associated with abnormal metabolic profiles. The current review will summarize the major changes in body composition and metabolic profiles that can lead to comorbidities such as type 2 diabetes mellitus and cardiovascular diseases after SCI. It is crucial for healthcare specialists to be aware of the magnitude of these changes. Such awareness may lead to earlier recognition and treatment of metabolic abnormalities that may reduce the co-morbidities seen over the lifetime of persons living with SCI.